Assessment of Serum Uric Acid Levels in Chronic Kidney Disease Patients: A Cross-Sectional Study in A Tertiary Care Hospital - Chand, Arun Bahadur; Sen, Bindu; Bhatt, Rajendra Dev; Bhatt, Mahendra Prasad; Cheetri, Santosh (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: Chronic kidney disease (CKD) is a major public health concern worldwide, notably impacting Nepal, where increased blood uric acid levels are common and may magnify the risks of glomerulosclerosis, interstitial fibrosis, and atherosclerosis. The purpose of this study was to measure uric acid levels among CKD patients at a Nepalese tertiary care hospital.Method: A cross-sectional study was conducted at the Kist Medical College and Teaching Hospital (KISTMCTH), Lalitpur, Nepal, on 242 CKD patients with stages IIIB to V from 14 April 2021 to 12 April 2024. Ethical approval was obtained from the Institutional Review Committee of KISTMCTH (Reference number: 42, 8/074/075IRC). Blood samples were collected, and uric acid and creatinine levels were measured using a fully automated biochemistry analyzer. Data analysis was performed using SPSS version 17.0.Results: Among the 242 CKD patients, hyperuricemia was found in 131(54.13%) patients with stage V CKD, 19(7.85%) patients with stage IV CKD, and 12(4.96%) patients with stage IIIB CKD. Hypouricemia was most common in stage V CKD, affecting 9 patients (3.72%), followed by stage IV, 3 patients, (1.24%), the majority of patients 163(67.36%) were adults (17-59 years). Of the 242 CKD patients, 179(73.97%) patients were in stage V, 38(15.70%) in stage IV, and 25(10.33%) in stage IIIB CKD patients. Out of the total CKD patients, 162(66.94%) had hyperuricemia, while 12(4.96%) had hypouricemia. Both hyperuricemia and hypouricemia were more common in males, with 97(40.08%) and 11(4.55%) of cases, respectivelyConclusion: Hyperuricemia is common among CKD patients, particularly in men. Hyperuricemia and hypouricemia were more prevalent among patients with stage V CKD.